Hubungan Kerja Keras dan Sikap Siswa dalam Pembelajaran IPA - Nirmala Sari; Yolanda Eka Putri; Nurdatul Jannah; Tari Okta Puspitasari (SEJ (Science Education Journal), 2019)
This study aims to determine the relationship of hard work to the attitudes of students in science subjects at SMPN 4 Muaro Jambi. The research design used is associative quantitative with correlation design. The sampling technique used was total sampling with a total sample of 126 students. The analysis technique used is descriptive statistics and inferential statistics. Descriptive statistics display the mean, mode, minimum and maximum values. While the inferential statistics used are product-moment correlation tests. Based on the results of this study, it was found that there is a relationship of hard work towards students' attitudes in science subjects that can be seen from the Sig. (2-tailed) of 0.010 <0.05 which states there is a relationship between attitude to student hard work. Then the correlation coefficient of 0.668 which states that the level of correlation is strong.